The perception of control as a predictor of emotional trends during gameplay. (April 2018) - Schrader, Claudia; Nett, Ulrike
Abstract: The present study investigated the effect of perceived control on trends of discrete achievement emotions during learning using a tower defense game designed for teaching human liver functionalities. A total of 124 students (Mage = 22.89 years; SDage = 3.01 years; 54.8% female) were randomly assigned to play one of three game versions (high, moderate or reduced control condition). The perception of control and achievement emotions, namely enjoyment, boredom, anger, and frustration, were assessed via questionnaire after each of three rounds of gameplay. Overall, autoregressive model analysis results revealed a significant relationship between control perception and each emotion in every round of play. Moreover, a closer look at the different game versions revealed significant interactions between game versions and rounds of play for control perception and for each of the four emotions. Compared to students in the game version with reduced control, students in the high and moderate control game version reported a higher perception of control and enjoyment and lower frustration and anger. However, these effects were not persistent over time of gameplay, which indicated an increase in gameplay competencies. As both the perception of control and discrete emotions dynamically change over time, an auto-dynamic adaptation of provided control to the actual changes and needs of players is a consideration for future research. Highlights: We investigated the role of control perception during learning with a serious game on achievement emotions. We examined trends of discrete achievement emotions during gameplay. The perception of control plays an important role for achievement emotions.